2018
DOI: 10.3348/kjr.2018.19.3.516
|View full text |Cite
|
Sign up to set email alerts
|

Nodule Classification on Low-Dose Unenhanced CT and Standard-Dose Enhanced CT: Inter-Protocol Agreement and Analysis of Interchangeability

Abstract: ObjectiveTo measure inter-protocol agreement and analyze interchangeability on nodule classification between low-dose unenhanced CT and standard-dose enhanced CT.Materials and MethodsFrom nodule libraries containing both low-dose unenhanced and standard-dose enhanced CT, 80 solid and 80 subsolid (40 part-solid, 40 non-solid) nodules of 135 patients were selected. Five thoracic radiologists categorized each nodule into solid, part-solid or non-solid. Inter-protocol agreement between low-dose unenhanced and stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…However, recent studies have reported that nodule classification and solid portion measurement are not substantially affected by CT protocols. 22,23 In this context, a large prospective study with uniform CT protocols and reproducible measurement tools (e.g., deep learning-based segmentation and quantification) is warranted. Fourth, the nodule type was primarily obtained from radiologic reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported that nodule classification and solid portion measurement are not substantially affected by CT protocols. 22,23 In this context, a large prospective study with uniform CT protocols and reproducible measurement tools (e.g., deep learning-based segmentation and quantification) is warranted. Fourth, the nodule type was primarily obtained from radiologic reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the observer variability for subsolid nodule classification is considerable (23,24). Although another recent study showed that nodule classification exhibits interchangeability between low-dose and standard-dose chest CTs (25), further investigation is needed regarding the variability of subsolid nodule classification in monoenergetic images with lower radiation dose, as used in our study.…”
Section: Discussionmentioning
confidence: 87%
“…Despite the heterogeneity of CT scan indications and acquisition protocols (both contrast and non-contrast scans were included) being considered as other methodological limitations, we can argue that all these circumstances are consistent with the routine practice of outpatient CT scan procedures. Interestingly, to the CT reading, Kyung Hee Lee and colleagues [ 19 ] found high agreement in nodule classification (subsolid and solid) between five thoracic radiologists for low-dose unenhanced CT and standard-dose enhanced CT.…”
Section: Discussionmentioning
confidence: 99%